Influence of renal function on treatment results after stroke thrombectomy - Laible, Mona; Möhlenbruch, Markus Alfred; Pfaff, Johannes; Jenetzky, Ekkehart; Ringleb, Peter A.; Bendszus, Martin; Rizos, Timolaos (Cerebrovascular diseases, 2017)
Background: Renal dysfunction (RD) may be associated with poor outcome in ischemic stroke patients treated with mechanical thrombectomy (MT), but data concerning this important and emerging comorbidity do not exist so far. Here, we investigated the influence of RD on postprocedural intracerebral hemorrhage (ICH), clinical outcome, and mortality in a large prospectively collected cohort of acute ischemic stroke patients treated with MT. Methods: Consecutive patients with anterior-circulation stroke treated with MT between October 2010 and January 2016 were included. RD was defined as glomerular filtration rate (GFR) <60 mL/min/1.73 m2. In a prospective database, clinical characteristics were recorded and brain images were analyzed for the presence of ICH after treatment in all patients. Clinical outcome was assessed by the modified Rankin Scale (mRS) after 3 months. To evaluate associations between clinical factors and outcomes uni- and multivariate regression analyses were conducted. Results: In total, 505 patients fulfilled all inclusion criteria (female: 49.7%, mean age: 71.0 years). RD at admission was present in 20.2%. RD patients were older and had cardiovascular risk factors more often. Multivariate regression analysis after adjustment for age, stroke severity, diabetes, hypertension, GFR, previous stroke, MT alone, or additional thrombolysis and recanalization results revealed that lower GFR was not independently associated with poor outcome (mRS 3-6; OR 1.13, 95% CI 0.99-1.28; p = 0.072) or ICH. However, lower GFR at admission was associated with a higher risk of mortality (OR 1.15, 95% CI 1.01-1.31; p = 0.038). Compared to admission, GFR values were higher at discharge (mean: 77.9 vs. 80.8 mL/min/1.73 m2; p = 0.046). Conclusions: We did not find evidence for an association of lower GFR with an increased risk of poor outcome and ICH, but lower GFR was a determinant of 90-day mortality after endovascular stroke treatment. Our findings encourage also performing MT in this relevant subgroup of acute ischemic stroke patients.